Effectiveness of Dialogical Patrol by the Turjawali Unit in the Samapta Unit for the Prevention of Illegal Liquor Circulation in the Polresta Jurisdiction of Sidoarjo - R, Bagus Muhammad (Advances in Police Science Research Journal, 2024)
The increase in the number of illegal alcohol distribution cases within the jurisdiction of the Sidoarjo City Police over the past three years has become a phenomenon that underlies this research. The Turjawali Unit of the Samapta Section, as the task executor, is responsible for mitigating this phenomenon through dialogical patrols. Therefore, this study was conducted to improve the effectiveness of the Turjawali Unit's dialogical patrols in preventing illegal alcohol distribution. The data presented in this qualitative research were obtained through observations, interviews, and document studies. The concepts used include the Concept of Effectiveness, the Concept of Public Security and Order, the Concept of Alcoholic Beverages, the Concept of Patrol, and the Concept of Samapta. The theories applied are SWOT Analysis Theory, Management Theory, Communication Theory, Competency Theory, and Crime Prevention Theory. Using these theories and concepts, the author identifies issues related to implementation, influencing factors, and the effectiveness of dialogical patrols. The author found that, in practice, planning products are still incomplete, organization is not yet based on personnel competence, dialogical patrol implementation has not covered distant areas, and supervision has not been carried out thoroughly. Additionally, the quality and quantity of personnel do not yet meet DSP standards, the scheduling is disproportionate due to a lack of personnel, the budget plan is not well-targeted, and there is a lack of adequate infrastructure. To address these issues, it is recommended that the Turjawali Unit of the Samapta Section of the Sidoarjo City Police prepare comprehensive planning by considering evaluation results, ensure task distribution based on personnel competence, and enhance the supervisory role of the Kasat when conducting dialogical patrols. The conclusion of this study is that the dialogical patrols conducted by the Turjawali Unit of the Samapta Section are not yet effective and face several challenges. The author suggests holding internal patrol training for members, implementing Timestamp and reporting through Google Forms and WhatsApp, as well as socializing Perkabaharkam Number 1 of 2017 concerning Patrols to the Turjawali Unit.